{ x2+y2-4x-3y+5=0 3x2+3y2-11x-7y+10=0

{ x2+y2-4x-3y+5=0 3x2+3y2-11x-7y+10=0
Гость
Ответ(ы) на вопрос:
Гость
Х2 + y2 - 4x - 3y + 5 = 0 - 3x2 - 3y2 + 12x + 9y - 15 = 0 3x2 + 3y2 - 11x - 7y + 10 = 0 X + 2y - 5 = 0 X = 5 - 2y X2 = 25 - 20y + 4y2 25 - 20y + 4y2 + y2 - 4( 5 - 2y ) - 3y + 5 = 0 5y2 - 20y + 25 - 20 + 8y - 3y + 5 = 0 5y2 - 20y + 5 + 5y + 5 = 0 5y2 - 15y + 10 = 0 5( y2 - 3y + 2 ) = 0 D = 9 - 8 = 1 y1 = ( 3 + 1 ) : 2 = 2 y2 = ( 3 - 1 ) : 2 = 1 X = 5 - 2y X1 = 5 - 4 = 1 X2 = 5 - 2 = 3 Ответ ( 1 ; 2 ) ; ( 3 ; 1 )
Не нашли ответ?
Ответить на вопрос
Похожие вопросы